THE RELATIONSHIP BETWEEN HISTORY OF HYPERTENSION AND ISCHEMIC ELECTROCARDIOGRAM FINDINGS IN CHRONIC HEART FAILURE PATIENTS - Maharani, Zahra; Ni Made Elva Mayasari; Santhy Annisa; Yudi Fadilah (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Heart failure is a condition in which the heart is unable to pump blood effectively throughout the body due to structural and functional impairments. It is a serious complication of hypertension, which can affect the heart's electrical activity and lead to abnormalities on electrocardiograms (ECG). This study aimed to determine the relationship between a history of hypertension and ECG abnormalities in chronic heart failure patients. This study used a cross-sectional study design, using primary data from ECG recordings, and ECG recording results interpreted by one expert. The study population included all chronic heart failure patients at the Cardiology Clinic of Muhammadiyah Palembang Hospital who met the inclusion and exclusion criteria. A total of 30 samples were analyzed. Among the patients, 25 (83,3%) had a history of hypertension. The results of the Fisher Exact Test statistical test between history of hypertension and abnormal ECG images obtained a value of p = 0,622 (p > 0.05). These findings indicate no association between a history of hypertension with ECG ischemic in chronic heart failure patients.